2011
DOI: 10.1159/000329818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Therapeutic Hypothermia in Neonates with Hypoxic-Ischemic Encephalopathy on Platelet Function

Abstract: Objective: Platelet dysfunction has been described in adults during hypothermia. We sought to determine whether it also occurs in neonates. Methods: We measured bleeding times and PFA-100 (platelet function analyzer) times in 10 neonates with hypoxic-ischemic encephalopathy during and after head cooling. Results: The 10 neonates were born at 38.2 ± 1.6 weeks’ gestation (mean ± SD), with birth weights of 3,222 ± 746 g, pH 6.79 ± 0.17, base excess –25 ± 8, and 10-min Apgar 4 ± 2. Cooling was instituted 111 min (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Other TEG variables including clot reaction time and coagulation index also trended in a direction consistent with the hypothesis that hypothermia slows enzymatic activity and impairs the coagulation cascade. Of interest, MA, which reflects platelet activity, did not vary based on temperature although there is known cold inhibition on platelet function (34). It should be noted that TEG may be insensitive to mild qualitative platelet dysfunction and likely more sensitive to platelet count (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Other TEG variables including clot reaction time and coagulation index also trended in a direction consistent with the hypothesis that hypothermia slows enzymatic activity and impairs the coagulation cascade. Of interest, MA, which reflects platelet activity, did not vary based on temperature although there is known cold inhibition on platelet function (34). It should be noted that TEG may be insensitive to mild qualitative platelet dysfunction and likely more sensitive to platelet count (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of platelets to form a hemostatically effective platelet plug [25] can be impaired in neonates receiving indomethacin [26] , ibuprofen (to a lesser extent) [27] , ampicillin [28,29] , inhaled nitric oxide [30] , or therapeutic hypothermia [31] . Moreover, large platelets function better than small platelets to form an effective platelet plug [24] .…”
Section: Guidelines For Administering Platelet Transfusions In the Nicumentioning
confidence: 99%
“…cTnI correlates strongly with the clinical grade of encephalopathy [7]. Hypothermia is linked to reduced cardiac output, peripheral vasoconstriction, sinus bradycardia, cardiac arrhythmias, hypotension, platelet dysfunction, and increased blood viscosity [8,9,10,11]. A study in newborn pigs showed a cardioprotective effect of hypothermia; whether this is also true in human infants is not clear [12].…”
Section: Introductionmentioning
confidence: 99%